Active Shiga-Like Toxin Produced by Some Aeromonas spp., Isolated in Mexico City - Palma-Martínez, Ingrid; Guerrero-Mandujano, Andrea; Ruiz-Ruiz, Manuel J.; Hernández-Cortez, Cecilia; Molina-López, José; Bocanegra-García, Virgilio; Castro-Escarpulli, Graciela (Frontiers in Microbiology, 2016)
Shiga-like toxins (Stx) represent a group of bacterial toxins involved in human and animal diseases. Stx is produced by enterohemorrhagic Escherichia coli, Shigella dysenteriae type 1, Citrobacter freundii and Aeromonas spp. Stx is an important cause of bloody diarrhea and hemolytic uremic syndrome (HUS). The aim of this study was to identify the stx1/stx2 genes in clinical strains and in outer membrane vesicles (OMVs) of Aeromonas spp., 66 strains were isolated from children who live in Mexico City and Shiga-like toxins effects were evaluated on Vero cell cultures. The capacity to express active, Stx1 and Stx2 toxins was determined on Vero cell cultures and the concentration of Shiga-like toxins was evaluated by lethal dose to 50% (LD50) assays, observing inhibition of damaged cells by specific monoclonal antibodies. The results obtained in this study support the hypothesis that the stx gene is another putative virulence factor of Aeromonas, and since this gene can be transferred horizontally through OMVs this genus should be included as a possible causal agents of gastroenteritis and it should be reported as part of standard health surveillance procedures. Furthermore, these results indicate that Aeromonas genus might be a potential causative agent of HUS.